2017
DOI: 10.1007/s00068-017-0854-y
|View full text |Cite|
|
Sign up to set email alerts
|

Traumatic inferior shoulder dislocation: a review of management and outcome

Abstract: Clinical and radiographic assessment of ISD is key to diagnosis and successful reduction. Patients can be treated with shoulder immobilisation for 2-3 weeks. In the setting of ongoing pain or instability, further imaging should be performed. The outcome of ISD is generally favourable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 32 publications
2
55
2
Order By: Relevance
“…Nambiar et al evaluated all of the published case reports regarding unilateral or bilateral LEH, and found that falls accounted for 45% of all cases, where falls from standing height accounted for 12% of all cases. 8 Reduction techniques for LEH have been described in the literature with the most common reduction technique being overhead traction. 7,9 This method involves bringing the patient's arm into full abduction and, with an assistant to provide counter traction, physician applies upward directed force.…”
Section: Discussionmentioning
confidence: 99%
“…Nambiar et al evaluated all of the published case reports regarding unilateral or bilateral LEH, and found that falls accounted for 45% of all cases, where falls from standing height accounted for 12% of all cases. 8 Reduction techniques for LEH have been described in the literature with the most common reduction technique being overhead traction. 7,9 This method involves bringing the patient's arm into full abduction and, with an assistant to provide counter traction, physician applies upward directed force.…”
Section: Discussionmentioning
confidence: 99%
“…Several immediate neurovascular complications may occur including brachial plexus, the axillary nerve and the axillary vessels [9,10]. Diagnosis and documentation of these complications before the reduction is compulsory from the medico-legal point of view and also for proper primary management of these injuries [11]. The pathomechanics of the luxatio erecta is well described in the literature: It involves hyper-abduction of the humerus [12].…”
Section: Discussionmentioning
confidence: 99%
“…The greater tuberosity was avulsed by the rotator cuff when the humeral head dislocated inferiorly [17]. Fourth, concerning the neurological injuries, there are present at approximatively in 60% of cases, most commonly to the axillary nerve probably due to traction at the point it passes through the quadrangular space [11,18]. All the three cords of the brachial plexus pass through the axilla and would be tethered in the dislocated position, and accordingly, our case presented the symptoms of hypoesthesia and muscle weakness over the right forearm and hand before closed reduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common causes of shoulder dislocations are due to electrical shock, extreme trauma and epilepsy [6]. Bilateral luxatio erecta is an extremely rare condition with 29 cases identified in the literature [7].…”
Section: Introductionmentioning
confidence: 99%